Probabilistic Seismic Analysis of the Deep Sliding Stability of a Concrete Gravity Dam-Foundation System - Hui Liang; Shengshan Guo; Yifu Tian; Jin Tu; Deyu Li; Chunli Yan (Advances in Civil Engineering)
There are various uncertainties in the design, construction, and operation of dams. These uncertainties have an important impact on the seismic response and seismic safety evaluation of concrete dams. In this research, a typical nonoverflow monolith of a concrete gravity dam is selected as a case study for the sliding stability analysis. Based on the analysis and demonstration of parameter sensitivity of friction coefficients and cohesion and their influence on the deep antisliding stability of the dam-foundation system, the probabilistic seismic analysis of a gravity dam-foundation system is carried out through Monte Carlo analysis with a large sample number. Damage levels are defined based on the sliding instability failure mode along with the corresponding threshold values of the damage index. Thus, seismic fragility analysis is investigated, and seismic fragility curves are obtained for the vulnerability assessment under earthquake hazards. The overall seismic stability of the gravity dam is evaluated, which provides the basis for the seismic safety evaluation in the probabilistic framework.